Pengaruh Proses Bubut Baja AISI 4140 terhadap Mental Workload dengan Metode NASA-TLX - Rahmi, Meri; Rachmatullah, Rachmatulllah; Sukardi, Casiman (Jurnal Rekayasa Mesin, 2021)
This study aims to analyze the mental workload with the experimental method when operating a lathe under two different conditions, namely by using cooling and without cooling. The material used as the specimen in this research is AISI 4140 material. Another important variable is the timing of the experiment in the morning and evening. This is related to the division of work shifts that often occurs in the manufacturing industry. The working time factor greatly affects work performance and vigilance at work. Based on the experimental results taken from 20 participants and processed with the NASA-TLX method, it shows that the mental workload in the lathe process with the addition of cooling is more significant than the lathe process without the addition of cooling, even though the data collection time is different. It is also directly proportional to the duration of the lathe process. So it can be concluded that the turning process is better to use cooling even on AISI 4140 Steel material because it does not require a high workload.